IMPACT OF ARTIFICIAL INTELLIGENCE ON PATENT LAW. - ANTONIO, SILVA; DALIA, PERKUMIENĖ; SIMONA, VRUBLEVICIŪTĖ (Humanities Studies, 2023)
According to Professor Klaus Schwab, the founder and head of the World Economic Forum, new and rapidly developing technologies are interconnected and complement each other in the physical, biological and digital spheres. In 2025 it is estimated that the preliminary amount of investments in the development and improvement of these technologies, including the annual increase in their value, which usually reaches 50 %, will rise to 35-50 billion US dollars. It is important to highlight that the number of patent applications related to artificial intelligence has increased significantly in recent years. A review conducted by the World Intellectual Property Organization notes that since the emergence of artificial intelligence in the 1950s, inventors have filed nearly 340,000 patents. Patent applications and published more than 1.6 million scientific publications on the topic of AI. In order to increase Europe's competitiveness in the fields of artificial intelligence research and implementation, the European Commission in 2018 published the European Artificial Intelligence Strategy, in which the following goals were set: promotion of the implementation of artificial intelligence in all areas of the economy, increasing the technological and industrial capacity of the European Union and preparing for economic and social changes, thus guaranteeing the proper functioning of legal and ethical systems. Also, in the same year, i.e. in 2018, by the decision of the European Commission, the European Artificial Intelligence Alliance was established to bring together various discussions and attract the participation of companies, consumer organizations, trade unions and representatives of civil society. In 2020 The European Commission presented an ambitious program published in the White Paper, the essence of which was to establish a pan-European approach to artificial intelligence. Artificial intelligence and computer systems based on it have long been used in most industries to automate and modernize all production. However, today these systems are becoming widely used in commercial industries as well. According to R. Abbot, a professor of law and medical sciences at the University of Surrey in the United Kingdom, artificial intelligence has recently been able to independently create inventions that can potentially be protected by patents. Despite this, many countries require that a natural person filing a patent application be listed as the inventor, but no legal framework has yet emerged to regulate the legal protection of inventions created by artificial intelligence (Abbot, 2019). The ongoing debate has also affected the World Intellectual Property Organization (WIPO), whose goal is a balanced and effective international intellectual property protection system that encourages innovation and creativity. The organization invited all member states to participate in a political debate on the impact of artificial intelligence on intellectual property rights. The third session discussed the most important questions of patent law: will there be a result of intellectual activity when an object has all the characteristics of patent law, but is autonomously created by artificial intelligence? Who will own the intellectual property rights to the invention created? During the discussion, Estonia, Latvia and Poland expressed their positions, but Lithuania has not yet spoken on this topic. In conclusion, the significance of the topic addressed in this scientific Article stems from the continually rapid progress of artificial intelligence technologies. This progress provides the opportunity for artificial intelligence to function as an inventor, creating innovations without human intervention. Considering the ongoing technological changes, it is suggested to update patent law systems and strive to balance the interests of society and artificial intelligence developers. Problematic question: can artificial intelligence be recognized as an inventor in the context of patent law? The purpose of the article: is to examine the impact of artificial intelligence on patent law. Object: the analysis of the legal system of patents, the regulation of which is influenced by artificial intelligence. Tasks: 1) examine the concept of the invention and compare patenting conditions in selected different jurisdictions; 2) analyze the current impact of artificial intelligence on Lithuanian patent laws and identify problems; 3) indicate the future prospects of artificial intelligence for the improvement of legal acts. Methods: linguistic (linguistic) - helps to understand the true meaning of the concepts and expressions used; systemic - helps to study patent law interacting with other legal systems; comparative - used to compare Lithuanian patent sources with European and other countries patent laws and court decisions; logical - integral in presenting conclusions and generalizations of thoughts.